Model Persamaan Struktural untuk Menganalisis Indikator Kesejahteraan Rumah Tangga - Rinaldi, Achi (Universitas Islam Negeri Raden Intan Lampung, 2019)
Welfare is an important thing that concerns all countries in the world, including Indonesia. Welfare is not only measured materially but also spiritually measured. Materially, welfare is measured by one's wealth, health, nutrition, education, assets, housing, and certain rights in society. While spiritually well-being is measured by perceived happiness. This study discusses the application of the structural equation model to examine the relationship between welfare indicators in Central Java Province. The model-built places education and employment as exogenous latent variables, while objective well-being and subjective well-being are endogenous latent variables. The data used to support the analysis were sourced from BPS, the results of the 2012 KOR National Social Economic Survey and MSBP, with a sample size of 6730 observations. The modeling results obtained by the model are quite feasible to explain the diversity of data, which is indicated by the value of GFI 0.97, AGFI 0.96, RMSEA 0.039, and RMSR 0.072. The analysis shows that education and employment have a direct influence on objective well-being and an indirect effect on subjective well-being. The effect of education on the level of welfare is higher than the effect of work.